Penerapan Uji Fungsionalitas Menggunakan Black Box Testing pada Game Motif Batik Khas Yogyakarta - Ariyana, Renna Yanwastika; Erma Susanti; Muhammad Rizqy Ath-Thaariq; Riki Apriadi (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
The development of game technology is growing rapidly, causing a lot of influence in people's lives. No exception in the field of culture. Games themselves can be used to introduce culture to society. However, when the application has been developed, it certainly needs to be tested. Carrying out functional tests on games that are being developed is of course very important to do, this is because by carrying out functional test errors, bugs or other problems related to functions in the game will be known. Performing functional tests using the black box test is one method that can be used in testing applications. Where the black box test can assist in identifying problems that occur when users use the system and assist developers in ensuring applications developed can be used easily and responsively, so as to ensure that applications that have been developed meet functional requirements, in accordance with the requirements and specifications that have been determined and can meet user expectations. In the research conducted, functional tests have been carried out on the Yogyakarta Typical Batik motif game, with the result that the game application developed can run according to its function and no bugs or errors were found when the system was used. Concluded that the game developed is feasible to use.